A Study on Bolton Anterior Tooth Size Discrepancies among Different Malocclusion Groups (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Aim: To investigate the correlation between anterior tooth size discrepancies among Angle's Class l, ll, lll malocclusions and corresponding normal occlusion, as well as their prevalence in Bangladeshi population. This study would act as a reference for diagnosis, treatment planning and assessment of prognosis in some orthodontic cases. Methods: This cross sectional study was conducted in the Department of Orthodontics & Dentofacial Orthopedics, Dhaka Dental College & Hospital. A total number of 200 subjects were selected in Angle's Class l, ll, lll and corresponding normal group. Each group had 50 subjects with males and females. A chi-square test was performed to statistically compare the prevalence of anterior tooth size discrepancies among Angle's Class l, ll, lll malocclusions and corresponding normal occlusion and two genders. Analysis of variance was used to compare the mean Bolton anterior tooth size ratios as a function of angle classification and gender. Statistical differences were determined at the 95% confidence level (p< 0.05). Results: No significant difference was observed in the mean Bolton anterior ratio between normal group and class-I malocclusion group (p = 0.343). Significant differences were observed between Class-II malocclusion and normal group (p=0.001), and also between Class-III malocclusion and normal group (p = 0.001). Individuals with Angle Class lll and Class ll malocclusions showed significantly greater prevalence of tooth size discrepancy than Class l malocclusion and corresponding normal group. Conclusion: The great diversity and ethnic mix of Bangladeshi population should alert our orthodontist to use Bolton analysis as an important diagnostic tool and become aware of the moderate variations that may be present and treated. It may somehow guide planning of this type of study in future. DOI: http://dx.doi.org/10.3329/bjodfo.v1i2.15982 Ban J Orthod & Dentofac Orthop, April 2011; Vol-1, No.2, 1-4